Sexology and philosophers of the body as political resistance to the new technical devices for the domination of humans at the beginning of the 20th century: Sade (Bloch) versus Richard von Kra!-Ebing (psychopathology) and Sigmund Freud (psychoanalysis) - Espinoza Lolas, Ricardo (2023)
This article dives into the beginnings of Freud's psychoanalysis and shows how the device of neurosis is invented as the essential to treat the cure of human suffering and in it a determination of our unconscious is generated that throughout the 20th century no longer resists, because in it everything that escapes from neurosis cannot be treated and neurosis itself is part of the human problem to be overcome. And as a result of this, this text shows that the human being does not allow himself to be trapped in the category of neurosis, but of the monstrous, and therefore every clinic in these times must be a clinic of the differentials that do not allow themselves to be delimited by any device.